2017
DOI: 10.1186/s40594-017-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Female senior secondary physics students’ engagement in science: a qualitative study of constructive influences

Abstract: Background: Prompted by fewer females compared to males enrolling in physics and advanced mathematics at both secondary and university levels, our research investigated the views and experiences of female students currently studying upper secondary school physics. We interviewed 18 female students about influences they considered important to their own science education, interest in science, and future science-related aspirations. Our purpose was to identify the experiences that these students most strongly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Those participants showed evidence of embodying growth mindsets [15,16]. These findings are consistent with studies conducted at the secondary school level that found that supportive teachers and the classroom culture influence student engagement in science; particularly for female students and those who have found themselves in non-supportive science cultures [17,18].…”
Section: Discussionsupporting
confidence: 83%
“…Those participants showed evidence of embodying growth mindsets [15,16]. These findings are consistent with studies conducted at the secondary school level that found that supportive teachers and the classroom culture influence student engagement in science; particularly for female students and those who have found themselves in non-supportive science cultures [17,18].…”
Section: Discussionsupporting
confidence: 83%
“…The students also referred to their parents as being supportive and providing opportunities that may have sparked their interest in science generally, and physics, specifically. 36 Finding from this study also showed that there was no gender difference regarding complementary congruence. Complementary congruence captures the situation when individuals perceive that their career exploration, planning, and goal setting need are met by their parents, and they perceive that parents are satisfied with their career-related progress.…”
Section: Discussionsupporting
confidence: 53%
“…The problem with fewer female students choosing to take advanced physics courses has been documented throughout the world, including Ghana (Buabeng et al., 2012), Scotland (Reid and Skryabina, 2003), Australia (Oliver et al., 2017), England, Singapore, Spain, and Mexico (Oon and Subramaniam, 2010). In the US, approximately 36% of undergraduate STEM degrees and 19% of undergraduate physics degrees were awarded to women in 2015 (American Physical Society, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers with rich content knowledge and enthusiasm toward teaching can result in positive gains in student motivation in physics (Keller et al., 2017). One recent study showed that female students’ motivation to study and do well in physics is linked to several factors, including having a combination of teachers, supportive and knowledgeable teachers, engaging pedagogy, the school’s science culture, and social interactions with family and peers (Oliver et al., 2017). In another study, students’ motivation in physics was positively related to the task-value they saw in the physics they were doing and interest in the science being studied (Wang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%